4(2x-1)+3(x-5)=14

Simple and best practice solution for 4(2x-1)+3(x-5)=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-1)+3(x-5)=14 equation:


Simplifying
4(2x + -1) + 3(x + -5) = 14

Reorder the terms:
4(-1 + 2x) + 3(x + -5) = 14
(-1 * 4 + 2x * 4) + 3(x + -5) = 14
(-4 + 8x) + 3(x + -5) = 14

Reorder the terms:
-4 + 8x + 3(-5 + x) = 14
-4 + 8x + (-5 * 3 + x * 3) = 14
-4 + 8x + (-15 + 3x) = 14

Reorder the terms:
-4 + -15 + 8x + 3x = 14

Combine like terms: -4 + -15 = -19
-19 + 8x + 3x = 14

Combine like terms: 8x + 3x = 11x
-19 + 11x = 14

Solving
-19 + 11x = 14

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '19' to each side of the equation.
-19 + 19 + 11x = 14 + 19

Combine like terms: -19 + 19 = 0
0 + 11x = 14 + 19
11x = 14 + 19

Combine like terms: 14 + 19 = 33
11x = 33

Divide each side by '11'.
x = 3

Simplifying
x = 3

See similar equations:

| 7.6x-3.7=-62.4 | | 4w*3= | | 3x+3=9x+18 | | 4/10=2/x | | 2x+x=3800 | | 5n/28-6/7=13/4 | | x/3-12=27 | | 2(x-3)/3 | | X(5x-4)=(5x+1)(x-3) | | 4x+6-x-9=3(x+5) | | 2x+13x=17+3 | | (z*10)-7=1 | | Senx=-0.22 | | 2x+3x=17+3 | | -4(3x-5)=-5x-20-3x | | n+4+39=95 | | y=5c | | F(x)=-X^4-x^3+1 | | 3v+8=23 | | M-6m+3m+1= | | 32=2a | | (12x)-(4x)-145320=100000 | | 3x+2y=1390 | | (2w-7)(3+w)=0 | | 32x=-2x+4 | | 7x+7=2(x-1) | | 3v+2=-13 | | x+(x*.67)=.075 | | -2(2X-1)+8X=8+2(5X-7) | | (7/5)y-6=-(2/3)y-(2/3) | | .4y=12 | | 14k-6k+-13k+20k-18k=12 |

Equations solver categories